"Black, white and gray"–A qualitative study of how Swedish police officers describe occupational knowledge. Issue 3 (25th November 2020) - Eliasson, Michelle Nathalie
Abstract : Purpose: The purpose of this study is to explore how Swedish police officers describe occupational knowledge. By learning more about how officers describe occupational knowledge, the study gives more insight about the types of information that they may be more likely to adopt in their occupational tasks. Design/methodology/approach: In this study, the author conducted 27 semi-structured interviews with Swedish police officers. I asked officers several open-ended questions about their everyday work life and professional experience. Findings: Swedish officers divide knowledge into two categories, which are theoretical knowledge and practical knowledge. Theoretical knowledge is learned in the academy and is described as "black and white, " meaning that it is considered static and not applicable to what happens out in patrol. Practical knowledge is learned in the field from colleagues. Research limitations/implications: Police officers around the world have a wide range of requirements and training to become police officers. However, empirical studies have found that officers tend to use different types of information when performing policing tasks. Depending on how information is perceived and is taught, officers may respond differently to different types of knowledge, due to their evaluation of the validity of the knowledge. Originality/value: The findings in this study support previous empirical studies on the area of policing and knowledge in two ways; first, this study argues that there is a categorization of knowledge among police officers. Second, this study suggests that officers view one occupational knowledge type as more theoretical and one as more practical.